Cute double sum

Calculus Level 5

If the closed form of n = 1 ( k = 1 n ( 1 ( 25 k 2 + 25 k + 4 ) ( n k + 1 ) 3 ) ) \sum_{n=1}^{\infty } \left (\sum_{k=1}^{n }\left (\dfrac {1}{(25k^2+25k+4)(n-k+1)^3}\right)\right) can be expressed as π a ζ ( b ) c + d e ζ ( b ) f \dfrac {\pi}{a } \zeta (b)\sqrt {c+\dfrac {d}{\sqrt e}}-\dfrac {\zeta (b)}{f} where b , d , e b,d,e are primes then find a + b + c + d + e + f a+b+c+d+e+f .

This problem was inspired by Prof. Daniel Sitaru's problem, Romania.

This problem is taken from Romanian Mathematical Magazine.

Note: ζ ( ) \zeta(\cdot) denotes the Riemann Zeta function .


The answer is 30.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rohan Shinde
May 29, 2019

Let ξ = n = 1 ( k = 1 n ( 1 ( 25 k 2 + 25 k + 1 ) ( n + 1 k ) 3 ) ) \displaystyle \xi=\sum_{n=1}^{\infty}\left(\sum_{k=1}^n \left(\frac {1}{(25k^2+25k+1)(n+1-k)^3}\right)\right)

Now writing the the total sum in different rows for each value of n n or interchanging the sums we get ξ = n = 1 1 n 3 k = 1 1 25 k 2 + 25 k + 1 = ζ ( 3 ) k = 1 1 25 k 2 + 25 k + 1 \displaystyle \xi =\sum_{n=1}^{\infty} \frac {1}{n^3}\sum_{k=1}^{\infty}\frac {1}{25k^2+25k+1}=\zeta(3)\sum_{k=1}^{\infty} \frac {1}{25k^2+25k+1}

ξ = ζ ( 3 ) 3 k = 1 ( 1 5 k + 1 1 5 k + 4 ) \xi =\frac {\zeta(3)}{3}\sum_{k=1}^{\infty}\left(\frac {1}{5k+1}-\frac {1}{5k+4}\right)

Let ξ 1 = k = 1 ( 1 5 k + 1 1 5 k + 4 ) = k = 1 0 1 ( 1 x 3 ) x 5 k d x \displaystyle \xi_1=\sum_{k=1}^{\infty}\left(\frac {1}{5k+1}-\frac {1}{5k+4}\right)=\sum_{k=1}^{\infty}\int_0^1 (1-x^3)x^{5k}dx

Interchanging the integral and the sum which is justified by Fubini's theorem and then using Geometric sum ξ 2 = 0 1 ( 1 x 3 ) x 5 1 x 5 d x \displaystyle \xi_2=\int_0^1 (1-x^3)\frac {x^5}{1-x^5}dx

Substituting x 5 = t x^5=t in ξ 2 \xi_2 we get

ξ 1 = 1 5 0 1 t 1 5 t 4 5 + 1 1 1 t d t \displaystyle \xi_1=\frac 15\int_0^1 \frac {t^{\frac 15}-t^{\frac 45} +1-1}{1-t}dt

Using the relation of Digamma function that ψ ( z + 1 ) + γ = 0 1 1 x z 1 x d x \displaystyle \psi(z+1)+\gamma=\int_0^1 \frac {1-x^z}{1-x}dx

we get ξ 1 = 1 5 ( ψ ( 9 5 ) ψ ( 6 5 ) ) \displaystyle \xi_1=\frac 15\left(\psi\left(\frac 95\right)-\psi\left(\frac 65\right)\right) Using the functional rule of Digamma function that ψ ( z + 1 ) = ψ ( z ) + 1 z \displaystyle \psi(z+1)=\psi(z)+\frac 1z we get ξ 1 = 1 5 ( ψ ( 4 5 ) ψ ( 1 5 ) 15 4 ) \displaystyle \xi_1=\frac 15\left(\psi\left(\frac 45\right)-\psi\left(\frac 15\right)-\frac {15}{4}\right) Using the Reflection formula of Digamma function that ψ ( 1 z ) ψ ( z ) = π cot ( π z ) \displaystyle \psi(1-z)-\psi(z)=\pi\cot(\pi z) we get that ξ 1 = 1 5 ( π cot ( π 5 ) 15 4 ) \displaystyle \xi_1=\frac 15\left(\pi\cot\left(\frac {\pi}{5}\right) -\frac {15}{4}\right)

Using this alongwith result of ξ \xi we get ξ = π 15 ζ ( 3 ) cot ( π 5 ) ζ ( 3 ) 4 \displaystyle \xi=\frac {\pi}{15}\zeta(3)\cot\left(\frac {\pi}{5}\right)-\frac {\zeta(3)}{4}

Using any trigonometric table or Wolfram alpha you can find that cot ( π 5 ) = 1 + 2 5 \cot\left(\frac {\pi}{5}\right)=\sqrt{1+\frac {2}{\sqrt 5}} So we get ξ = π 15 ζ ( 3 ) 1 + 2 5 ζ ( 3 ) 4 \displaystyle \xi=\frac {\pi}{15}\zeta(3)\sqrt{1+\frac {2}{\sqrt 5}}-\frac {\zeta(3)}{4}

Hence the answer 30 \boxed {30}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...